2014
DOI: 10.1016/j.jcf.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of switching to the new global lung function initiative equations on spirometry results in the UK CF Registry

Abstract: A unified approach to interpreting spirometric lung function measurements would help facilitate more appropriate comparison both within and between centres and countries. Interpretation of longitudinal measurements using a continuous reference equation across all-ages, like the GLI, may further improve our understanding of CF lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…This suggests that the reference population is not perfectly representative, as we would not expect measures from children with CF (even with ‘normal’ lung function) to substantially exceed those predicted by a representative reference population. Although a recent study identified subgroups of children with CF where GLI and Wang reference equations provide different FEV 1 and FVC percent predicted results, 17 we did not find appreciable differences depending on equation used within our narrow age-range cohorts (Figure 5; available at www.jpeds.com), suggesting that the above normal FEV 1 and FVC distributions we observed in screened children are not peculiar to GLI reference equations.…”
Section: Discussioncontrasting
confidence: 63%
“…This suggests that the reference population is not perfectly representative, as we would not expect measures from children with CF (even with ‘normal’ lung function) to substantially exceed those predicted by a representative reference population. Although a recent study identified subgroups of children with CF where GLI and Wang reference equations provide different FEV 1 and FVC percent predicted results, 17 we did not find appreciable differences depending on equation used within our narrow age-range cohorts (Figure 5; available at www.jpeds.com), suggesting that the above normal FEV 1 and FVC distributions we observed in screened children are not peculiar to GLI reference equations.…”
Section: Discussioncontrasting
confidence: 63%
“…A previous study found a near-linear %FEV 1 decline from childhood to adulthood with GLI equation, whereas there was accelerated %FEV 1 decline during adolescence and young adulthood when %FEV 1 was calculated with Knudson equation 21 . One advantage of using the GLI equation, which is seamless across all ages, is that it improves the interpretation of %FEV 1 decline 21, 22 . Another advantage is that %FEV 1 decline can be adjusted for baseline %FEV 1 using ESCF reference values (since the ESCF values for %FEV 1 decline were calculated using the GLI equation 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It excites the interest of nearly all major pulmonological associations (and not only). Publications show that not always can the GLI2012 proposal be recognized as the ‘gold standard’ (Stanojevic et al ., ) for various ethnic groups.…”
Section: Discussionmentioning
confidence: 99%